A Heavenly Home for the Homeless: Aliens and Strangers in 1 Peter - Chin, Moses (Tyndale bulletin, 1991)
A re-examination of the evidence use by J. H. Elliott to ascertain the meanings of the terms πάροικος and παρεπίδημος in 1 Peter.